Synthesis of Indium Nitride Epitaxial Layers on a Substrate of Porous Indium Phosphide - J.A. Suchikova (Журнал нано- та електронної фізики)
The paper presents a technique to obtain InN films on porous InP substrates by radical-beam gettering epitaxy. According to the results of the Auger spectroscopy, InN film thickness ranged from 100 nm to 0.5 microns depending on the etching conditions.